(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article analyses the current legislation of Ukraine and doctrinal approaches to the concept of court decisions. The features of court decisions are revealed. A critical analysis of the definition of the term “decision” is made and recommendations for improvement of current legislation are provided. The study indicates that today there is a rather illogical situation, since the Civil Procedure Code of Ukraine defines the term “judgment” in two ways: as a procedural document by which a civil case is resolved on the merits; and as a general concept for all acts of justice adopted by a court in civil proceedings. It is noted that in order to eliminate such terminological inaccuracies, it is necessary to amend the current legislation. The following types of court decisions are thoroughly analysed: decisions on recognition, decisions on award and transformative (constitutional) decisions. It is noted that award judgments are court decisions confirming the rights, obligations and legitimate interests of the parties, in which one party undertakes to perform certain actions in favour of the other or to refrain from performing them; recognition judgments are court decisions confirming the existence or absence of certain legal relations, circumstances or legal facts between the parties; constitutional judgments are court decisions aimed at creating new legal relations, changing or terminating existing legal relations. The following types of court decisions are analysed: supplementary decision, decision in absentia, full decision and abridged decision. The conclusion is made that studying and analysing the concept and types of court decisions is of great scientific and practical importance, since court decisions stabilise legal relations and ensure real, proper and timely protection of rights and interests protected by law.